Higher Frequencies of Lymphocytes Expressing the Natural Killer Group 2D Receptor in Patients With Behçet Disease - Bonacini, Martina; Soriano, Alessandra; Zerbini, Alessandro; Calò, Eleonora; Cimino, Luca; Muratore, Francesco; Fontana, Luigi; Braglia, Luca; Parmeggiani, Maria; Salvarani, Carlo; Croci, Stefania (Frontiers in Immunology, 2018)
Behçet disease (BD) is an inflammatory systemic disease with a fluctuating course, which can affect the skin, eyes, central nervous system, musculoskeletal, gastrointestinal and vascular systems. No laboratory tests are currently available for the diagnosis of BD and monitoring disease activity. Moreover there is a lack of knowledge on BD pathogenesis. This study focused on circulating Natural Killer (NK), NKT and T cells evaluated as CD3neg CD56pos, CD3pos CD56pos and CD3pos CD56neg. Peripheral blood mononuclear cells (PBMCs) were collected from 38 BD patients and 20 Healthy controls (HC). The frequencies of NK, NKT and T cells expressing CD16, CD69, NKG2D, Nkp30, Nkp46 and NKG2A were assessed by flow cytometry. Cytotoxic potential of NK cells was evaluated by flow cytometry as the percentage of cells expressing the degranulation marker CD107a after incubation with K562 cells. The levels of 27 cytokines were determined in plasma with a multiplex bead-based assay. Higher percentages of NK, NKT and T cells expressing NKG2D were detected in PBMCs of BD patients than HC. ROC curve analysis showed that the evaluation of NKG2Dpos NK, NKT and T cell percentages discriminated between BD patients and HC. Moreover, there was a positive correlation between the BD Current Activity Form (BDCAF) scores and the frequencies of NKG2Dpos NK and NKT cells. A higher frequency of NK cells expressing CD107a was induced in PBMC from BD patients than HC after incubation with K562 cells. Concentrations of IL-5, IL-6, IL-10, IL-13, IP-10 and MIP-1β were higher in plasma of BD patients than HC. Monitoring the frequencies of NKG2Dpos lymphocytes could help the clinicians in BD patients management. In addition, the increased expression of NKG2D in BD patients is likely involved in disease pathogenesis.